POTENCY OF DREGS COCONUT FERMENTATION (COCOS NUCIFERA) AS AN ALTERNATIVE FEED FOR FISH AND POULTRY 'PA-BIO’ - Yolanda Fitria Syahri; S. Syahrir (Agrotech Journal, 2016)
People of Kolaka accustomed to using coconuts as well be used as a food supplement or a mixture of additives in processed foods, cakes and other confectionary. Therefore utilizing coconut pulp as feed fish and poultry should be made to minimize the potential for household waste. Feed from coconut pulp is a transfer of science and technology to the people who are expected to help poor people to be productive. Fermentation is one method to process coconut pulp into feed ingredients. The fermentation process is done by using spores of Aspergillus niger. The fermentation process is done in stages, by aerobic fermentation followed by anaerobic fermentation (enzymatic process). In short the process of making feed "PA-BIO" from coconut pulp is: Dregs of coconuts added water, stirred and steamed. Cooled and then stirred together with a mixture of minerals, Aspergillus niger spores are added and stirred again until evenly distributed. The mixture was then fermented aerobically and unaerobically. Dregs fermented and then dried and packaged for later in packing. Based on the results of research that the utilization of coconut dregs as cattle feed and fish is potential. Miskiyah et al. (2006), increase protein content after fermentation of coconut pulp 11.35% to 26.09%, or by 130% and decreased fat content of 11.39%. The results also showed that the feed produced quite safe for livestock, namely the aflatoxin content 20 ppb. Feed from coconut pulp is also good for fish farming. Goenarso et al. (2002) on tilapia (Oreochromis niloticus L.), the faster fish growth with increasing the feed protein content of 25%, 30%, 35%, 40% and 45%.